Factors affecting the occupational accident rates among nurses - Ülfiye Çelikkalp; Filiz Dilek (SciELO, 2019)
ABSTRACT Objective: In this hospital-based study, we aimed to determine occupational accident perceptions and occupational accident reasons in sample of Turkish nurses. Method: In the study, the Epworth Sleepiness Scale, the Workload Scale and a Study Questionnaire Form including the employment characteristics of the nurses, their socio demographic characteristics, and the occupational accidents they encountered. Results: 108 nurses (90 females, 18 males; mean age, 26.42±5.5 years) participated in the study. 68.5% of nurses have undergone at least once a occupational accident. Most of the participants were found to have experienced occupational accidents with approximately half evaluating their occupational accidents risk as high. Most of the nurses worked overtime and in shifts. The mean total scores for the Epworth Sleepiness Scale and Workload Scale were respectively 9.09±3.33 and 36.94±6.42. Statistically significant differences in occupational accidents were found with regard to Epworth Sleepiness Scale and Workload Scale scores, working in shifts, and working overtime (p<0.05). Conclusion: It was concluded that nurses had very high rates of occupational accidents and that the heavy work conditions affected occupational accidents.